Applications of the channel flow cell for UV-visible spectroelectrochemical studies .2. Transient signals - Wang, R; Tam, K; Marken, F; Compton, R (1997)
The use of the channel flow cell for ultraviolet-visible (UV-vis) spectroelectrochemical experiments has been developed to determine the diffusion coefficients of electrogenerated species by means of monitoring the transient absorbance response resulting from a potential step at a working electrode immediately upstream of the incident spectrophotometric beam. The technique is applied to measure the diffusion coefficient of tris(4-bromophenyl)amine (TBPA) radical cation in acetonitrile at 25°C. It is shown that the diffusion coefficient of electrogenerated TBPA radical cation (1.64 ± 0.02 × 10-5 cm-2 s-1) is very close to that of the parent molecule (1.57 ± 0.03 × 10-5 cm2 s-1).